Eating tomorrow : agribusiness, family farmers, and the battle for the future of food - Wise, Timothy A., 1955- (The New Press, 2019)
Most of the world, Wise reveals, is fed by hundreds of millions of small-scale farmers, people with few resources and simple tools but a keen understanding of what and how to grow food. These same farmers<U+2014>who already grow more than 70 percent of the food eaten in developing countries<U+2014>can show the way forward as the world warms and population increases. Wise takes readers to remote villages to see how farmers are rebuilding soils with ecologically sound practices and nourishing a diversity of native crops without chemicals or imported seeds. They are growing more and healthier food; in the process, they are not just victims in the climate drama but protagonists who have much to teach us all.